UJI AKTIVITAS ANTIJAMUR EKSTRAK ETANOL KULIT BUAH PETAI (PARKIA SPECIOSA HASSK.) TERHADAP PERTUMBUHAN CANDIDA ALBICANS DAN MICROSPORUM GYPSEUM - Luzhny Azzahra; Lanny Mulqie; Ratu Choesrina (Bandung Conference Series: Pharmacy, 2023)
Abstract. Petai plant (Parkia speciosa Hassk.) is known to contain metabolite compounds that can be developed to treat several diseases, one of which is antifungal. This study aims to determine the antifungal activity of ethanol extract of petai fruit peel (Parkia speciosa Hassk.) against the growth of Candida albicans and Microsporum gypseum, and determine the value of the inhibition zone in ethanol extract of petai fruit peel (Parkia speciosa Hassk.) against the growth of Candida albicans and Microsporum gypseum. The method used was agar diffusion (wells). The concentrations of the extracts tested were 1, 5, 10, 15, and 20%. The positive control used was ketoconazole 2% and the negative control was DMSO. The results of the calculation of the average zone of inhibition of ethanol extract of petai fruit peel against Candida albicans at concentrations of 1, 5, 10, 15, and 20% were 13,9; 15,5; 17,6; 18,9; and 20,3 mm, respectively. The results of the calculation of the inhibition zone of ethanol extract of petai fruit peel against Microsporum gypseum at concentrations of 1, 5, 10, 15, and 20% were 17,5; 19,8; 18,6; 23,7; and 26,6 mm, respectively. The results showed that ethanol extract of petai fruit peel (Parkia speciosa Hassk.) has antifungal activity with the formation of an inhibition zone around the wells. Abstrak. Tanaman petai (Parkia speciosa Hassk.) diketahui memiliki kandungan senyawa metabolit yang dapat dikembangkan untuk mengobati beberapa penyakit, salah satunya antijamur. Penelitian ini bertujuan untuk mengetahui aktivitas antijamur ekstrak etanol kulit buah petai (Parkia speciosa Hassk.) terhadap pertumbuhan Candida albicans dan Microsporum gypseum, serta mengetahui nilai zona hambat pada ekstrak etanol kulit buah petai (Parkia speciosa Hassk.) terhadap pertumbuhan Candida albicans dan Microsporum gypseum. Metode yang digunakan adalah difusi agar (sumuran). Konsentrasi ekstrak yang diuji yaitu 1, 5, 10, 15, dan 20%. Kontrol positif yang digunakan yaitu ketokonazol 2% dan kontrol negatif yaitu DMSO. Hasil perhitungan rata-rata zona hambat ekstrak etanol kulit buah petai terhadap Candida albicans pada konsentrasi 1, 5, 10, 15, dan 20% berturut-turut sebesar 13,9; 15,5; 17,6; 18,9; dan 20,3 mm. Hasil perhitungan zona hambat ekstrak etanol kulit buah petai terhadap Microsporum gypseum pada konsentrasi 1, 5, 10, 15, dan 20% berturut-turut sebesar 17,5; 19,8; 18,6; 23,7; dan 26,6 mm. Dari hasil penelitian menunjukkan ekstrak etanol kulit buah petai (Parkia speciosa Hassk.) memiliki aktivitas antijamur dengan terbentuknya zona hambat disekitar sumuran.